Copper Phthalocyanine Chemiresistors as Industrial NO2 Alarms - Hadi AlQahtani; Mohammad Alshammari; Amjad M. Kamal; Martin Grell (Sensors)
We present a chemiresistor sensor for NO2 leaks. The sensor uses the organometallic semiconductor copper(II)phthalocyanine (CuPc), and is more easily manufactured and characterised than previously described organic transistor gas sensors. Resistance R is high but within the range of modern voltage buffers. The chemiresistor weakly responds to several gases, with either a small increase (NH3 and H2S) or decrease (SO2) in R. However, the response is low at environmental pollution levels. The response to NO2 also is near-zero for permitted long-term exposure. Our sensor is, therefore, not suited for environmental monitoring, but acceptable environmental pollutant levels do not interfere with the sensor. Above a threshold of ~87 ppb, the response to NO2 becomes very strong. This response is presumably due to the doping of CuPc by the strongly oxidising NO2, and is far stronger than for previously reported CuPc chemiresistors. We relate this to differences in the film morphology. Under 1 ppm NO2, R drops by a factor of 870 vs. non-polluted air. An amount of 1 ppm NO2 is far above the ‘background’ environmental pollution, thereby avoiding false alarms, but far below immediately life-threatening levels, thus giving time to evacuate. Our sensor is destined for leak detection in the nitrogen fertiliser industry, where NO2 is an important intermediate.